ROSARIO VERA PEÑALOZA AN EDUCATOR THAT SWAYED INTO ARGENTINEAN TEACHING HISTORY - Vera de Flachs, María Cristina (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2013)
This article’s rationale aims to reconsider Rosario Vera Peñaloza’s lifetime and work. A former educator who has undoubted been a main reference in Argentinean teaching process through her existence. To fulfill this task we had analyzed different authors ‘devoted  work about her as well as her own master pieces.